Influence of samarium doping on magnetic and structural properties of M type Ba–Co hexaferrite. Issue 7 (15th May 2016) - Rana, Kush; Thakur, Preeti; Thakur, Atul; Tomar, Monika; Gupta, Vinay; Mattei, Jean Luc; Queffelec, Patrick
Abstract: Sm doped Ba–Co hexaferrite with composition BaCo0.8 Sm x Fe(11.2−x) O19 ( x =0.2, 0.4 and 0.6) were prepared via a citrate precursor method. After appropriate heat treatments, the ferrite samples were characterised by using different measurement techniques. X-ray diffraction (XRD) confirmed the formation of M phase with an average crystallite size of 35–45 nm. Observed tensile strain leads to the elongation of Ba–Co grains and was calculated using Williamson Hall plot. Surface morphology of these samples was studied by using field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). σ – H loops of these samples were measured at room temperature up to an applied field of 22, 000 Oe using vibrating sample magnetometry (VSM). With an increase in concentration of Sm ions in Ba–Co lattice, specific saturation magnetisation ( σ s ), coercivity ( H c ) and retentivity ( σ r ) values were found to decrease. At x =0.2, excellent values of H c (2690.20 Oe) and squareness ratio (SQR=0.5619) were simultaneously found. These parameters make this material a promising candidate for the applications such as high density magnetic recording and enhanced memory storage.